Changes in angular momentum during the golf swing and their association with club head speed - Izumoto, Y.; Kurihara, T.; Sato, T.; Maeo, S.; Sugiyama, T.; Kanehisa, H.; Isaka, T. (International Journal of Performance Analysis in Sport, 2020)
This study measured changes in angular momentum during a golf swing and determined its associations with club head speed (CHS). Three-dimensional coordinates of anatomical landmarks were obtained during driver shots in 17 male collegiate golfers. A 15-segment model was used to calculate total (body-club system) angular momentum about the whole-body centre of mass and the segmental contributions of the trunk, arms, legs, and club to CHS. Angular momentum of the body-club system and the club increased from the top of the backswing towards ball impact. While angular momentum of the arms reached a maximum before the middle downswing, that of the trunk peaked after the middle downswing. The trunk maximum angular momentum was selected as the sole contributor for CHS (R2 = 0.494, p = 0.002). CHS negatively correlated with the relative difference between maximum angular momentum and angular momentum at impact only in the trunk (r = -0.492, p = 0.045). These results suggest that 1) the club head is accelerated by increasing angular momentum of the body-club system without sequential motion from the proximal (trunk) to distal (arm) segments, and 2) gaining large trunk angular momentum in the later part of the downswing is essential for fast CHS.